PERBANDINGAN HASIL BELAJAR FISIKA MATERI POKOK LISTRIK DINAMIS DENGAN MENGGUNAKAN METODE PROBLEM SOLVING DAN METODE DEMONSTRASI DI KELAS X SMA NEGERI PADANGSIDMPUAN - Asmaidah, Seri (Jurnal Physics Education (PhysEdu), 2023)
This study aims to describe the learning outcomes of the subject matter physics dynamic power by using problem solving method in class X SMA Negeri 1 Padangsidimpuan, to describe the subject matter of physics learning outcomes in the classroom dynamic power X SMA Negeri 1 Padangsidimpuan, and to see whether there are differences learning outcomes of the subject matter physics dynamic power by using problem solving and demonstrations in class X SMA Negeri 1 Padangsidimpuan. This research was conducted using the experimental method to see the difference of implementation measures. The population in this study were all students of Class VII SMA Negeri 1 Padangsidimpuan which consists of 6 classes totaling 190 people. The sampling technique used was cluster random sampling technique, so that the sample obtained as many as 64 people. The class was taken is X-3 and X-5The data collected were analyzed in two ways : first descriptive analysis to look at the general picture of the two variables, and then to determine whether there are differences between the two variables we used t - tests to test Suharsimi. As for the necessary data capture is done with the test. In order to obtain data regarding the subject matter of physic learning outcomes using the dynamic power of problem solving and demonstrations. Learning outcomes of the research dynamic power by using problem solving methods obtained an average of 73.33. If consultation with the assessment criteria in Table 3 Chapter III is the category of "Good”. While the value of the subject matter of physics learning dynamic power by using demonstration method obtained an average of 70.00. If consulted in table 3 Chapter III is the category of "Good “. Based on calculations performed earned value "t" of 1.69, whereas the 5 % significance level and df = n1 + n2 - 2 = 32 + 32 = 64-2 = 62. Ttabel value at significant level of 5 % of 64 is 1.66. Based on the calculation above, it can be concluded that t is greater than t table ( t > table = 1,69 > 1,66). Means that the hypothesis is upheld in this study can be accepted or approved. This means that there Comparison of Learning Outcomes Topic Electricity Physics Dynamic Method Using Problem Solving and Demonstration in Class X SMA Negeri 1 Padangsidimpuan.